(3GdNQjWI GdJGQjNjI dOhd GdESdGes - (3QRb Gddg efbQjhSs ((3eOjfI GdefjG s)
(3ChdgG (B:s
(3HOCJ HHjGf eaJGMgG , Hbhdg (B: (3gPg GdNQjWI JMJhi Ydi JGQjN GdOhd GdESdGejI hJHJOF ef SfI (B561(3e Edi hbJfG GdMGVQ , eY edGMXI GdEYJHGQGJ GdBJjI (B: (3ChdkG (B_ (3jeQ HCYdi GdNQjWI ef ChdgG Edi BNQgG s
(3ef CjGe GdfHi Udi Gddg Ydjg hSde Edi gPg GdCjGes
(3cJHgG eDdagG ai Gdjhe GdNGeS hGdYTQjf ef TgQ SHJeHQ SfI (B1932(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs